Radiation therapy to the primary tumor for de novo metastatic breast cancer and overall survival in a retrospective multicenter cohort analysis. (April 2020) - Pons-Tostivint, Elvire; Kirova, Youlia; Lusque, Amélie; Campone, Mario; Geffrelot, Julien; Rivera, Sofia; Mailliez, Audrey; Pasquier, David; Madranges, Nicolas; Firmin, Nelly; Crouzet, Agathe; Gonçalves, Anthony; et al.
Highlights: ERT was commonly performed in dnMBC patients despite the absence of guidelines. This is the largest study evaluating the impact of ERT on OS in dnMBC patients. ERT and BMT were associated with reductions in the hazard of death compared with no LRT. ERT could be an appropriate locoregional treatment in selected dnMBC patients. Abstract: Background: The impact of locoregional treatment (LRT) on overall survival (OS) in de novo metastatic breast cancer (dnMBC) is still under debate, with very few data available regarding exclusive radiotherapy (ERT) as a therapeutic modality. Methods: We evaluated the impact of ERT, exclusive surgery, or a combination of surgery plus radiotherapy (bimodality therapy, BMT) on survival outcomes in a national real-life dnMBC cohort. The primary and secondary end points were OS and progression free survival (PFS) according to LRT (ERT, exclusive surgery, BMT) and no LRT. Sensitivity analyses were performed using propensity score matched analyses. Results: From 2008 to 2014, 4507 dnMBC patients were identified. Only patients alive and free from progression under systemic therapy at least 1 year after diagnosis were included ( n  = 1965). Forty-five percent of patients (891/1965) underwent LRT: 41.1% ( n  = 366) ERT, 13.7% ( n  = 122) exclusive surgery, and 45.2% ( n  = 403) BMT. OS adjusted for major prognostic factors was significantly longer in the ERT and BMT group compared with no-LRT group, but not exclusive surgery (hazard ratio (HR) = 0.63, 95% confidence interval (CI) [0.49, 0.80], p  < 0.001, HR = 0.61, 95%CI [0.47, 0.78], p  < 0.001 and HR = 0.87, 95%CI [0.61, 1.26], p  = 0.466 respectively). Results were similar after matching on a propensity score. ERT, surgery and BMT were all associated with a significantly better PFS in multivariable analysis. Conclusion: ERT was significantly associated with better OS in dnMBC, in the same magnitude as BMT, compared with no-LRT. However, even with statistical models adjusted for known prognostic factors and propensity score analysis, selection biases cannot be eliminated from observational studies.